Аnna Sahakyants in the Work and Writings on Tsvetaeva and not only (with Fragments of Letters, 1965-2000) - GONCHAR, NATALYA (Bulletin of Yerevan University H: Russian Philology, 2021)
Тhe investigation and interpretation of Marina Tsvetaeva’s life and creative work took the main place in almost half a century literary work of Anna Saakyants. As a devoted companion of poet’s daughter, Ariadna Efron, she made ready first publications and editions of Tsvetaeva in USSR, and subsequently, also up to Tsvetaeva’s collected works in 7 volumes (1996). The fundamental (over 800 pp.) book of A.Sahakyants “Marina Tsvetaeva. The Life and Work” (1997) became the total result of her many years studies and writings on the beloved literary figure. The author of this article presents a long and efficient path traversed by Sahakyants in the indicated direction, evaluates her contribution in Tsvetaeva-sphere, also pays attention on other sides of Sahakyants life and work. Many fragments of letters (1965-2000) are published in the article for illustration.